Integrasi Aktivitas Belajar Tri Hita Karana Berorientasi 4C dalam Mata Kuliah Konsep Dasar IPA SD - I Made Ari Winangun (Edukasi: Jurnal Pendidikan Dasar, 2023)
This study aims to integrate the 4C-oriented Tri Hita Karana learning activities in the Elementary Science Basic Concepts course in: (i) initial activities; (ii) core activities; and (iii) closing activities. The results of this literature review, namely: (i) the integration of learning activities in the initial activities carried out by paying attention to the learning environment, learning resources, and the readiness of educators and students from both psychological and cognitive aspects; (ii) the integration of learning activities into the core activities is carried out by conveying learning objectives, presenting natural phenomena, carrying out technical learning according to the design or lesson plans, and concluding lessons; and (iii) the integration of learning activities in closing activities is carried out by maintaining the learning environment, assessing the learning process, and submitting the next learning plan. The three forms of learning activities implement Tri Hita Karana-based educational and teaching values, namely religious, spiritual, humanist, democratic, nationalist, environmental aesthetics, and ecological and are oriented towards creativity and innovation, critical thinking and problem solving, collaboration, communication ( 4C)